A feasibility analysis of the use of the Skipworth model for Bridgetown Water Supply Network and a Whole Life Costing to compare the water distribution systems at Greenvale pumping station - Shukla, Raghupati (Curtin University, 2012)
To promote efficient use of water resources in the developing world, there is a recognized need to make the best use of infrastructure developments and application of Whole Life Costing (WLC) in combination with computational optimization. In this way the efficiency of Water Management in public and private areas can be improved. This case study, a feasibility study and whole life costing analysis, was designed to assess the feasibility of the Skipworth model on the Bridgetown Water Supply Network.The Skipworth model was proved to be more cost effective than the current models used by the Water Corporation at Bridgetown. The whole life costing was conducted with Greenvale Pumping Station in order to compare the water distribution methods, Pump, Gravity and Combined Systems. The feasibility studies provided much information to the Water Corporation and Water Organizations of Australia to enable changes in the existing Water Distribution System of Australia. The whole life costing provided data which proved the Gravity and Combined systems were more cost effective than the current Pumping system. Recommendations were made for the implementation of the Skipworth model at Bridgetown and a Gravity and Combined system at Greenvale.